Exploring teacher knowledge and actions supporting technology-enhanced teaching in elementary schools: Two approaches by pre-service teachers - Figg, Candace; Jamani, Kamini Jaipal (Australasian Journal of Educational Technology, 2011)
Two approaches to teaching with technology to highlight practice-based teacher knowledge and actions for teaching technologically enhanced lessons are presented. Participants were two elementary pre-service teachers teaching during practicum. Qualitative data sources included verbatim transcripts of participant interviews, field notes of planning and support sessions, and classroom observations. Teacher lesson plans and student work samples triangulated data. Cross case analysis revealed that content-centric pedagogy - focusing lesson design on a specific content learning outcome, rather than technical skill - promoted student engagement and learning of both content and technical skill. Additionally, some pedagogical knowledge characteristics, reflected in specific teacher actions related to planning and implementation of technology-enhanced lessons, were fundamental across the two subject areas investigated. For novice elementary teachers, explicit communication of generic technology pedagogical knowledge characteristics, supported by concrete examples of teacher actions, may contribute to teachers experiencing a degree of success during their initial attempts at teaching with technology.